Analysis of Different Control Approaches for a Local Microgrid: A Comparative Study - Haque, Abrarul; Kholilullah, Ibrahim; Sharma, Anik; Mohammad, Ashif; Khan, Saidul Islam (Control Systems and Optimization Letters, 2024)
An analysis that contrasts various methods for managing a microgrid's operations in a community context is known as comparison research on control strategies for community microgrids. The study's objectives are to evaluate the benefits and drawbacks of various control schemes and to pinpoint the best approach for enhancing the microgrid's performance. Control methods include islanded mode control, hybrid mode control, grid-connected mode control, and advanced control strategies that combine economic dispatch with optimum power flow are usually compared in the research. A comparison is established. Depending on elements including resilience, cost-effectiveness, efficiency, stability and dependability. The comparative study's findings shed light on the optimal control approach for a particular community microgrid taking into account the resources that are available, the local energy consumption, and other variables. This review also emphasizes the advantages of using advanced control systems, these systems maximize energy management, maintain grid stability, and improve overall system performance by controlling the intricate interactions among distributed energy resources (DERs), such as solar photovoltaics, wind turbines, energy storage, and conventional generators. Energy efficiency will be increase in rural locations with high solar radiation and limited wind power by using advanced methods and grid-connected mode management. Demand response reduces dependency on external grids and associated expenses while improving resilience. Customized control strategies are essential for maximizing community microgrid performance. There includes discussion of a number of control systems, including distributed control, grid-forming control, energy management and optimization, frequency and voltage regulation, islanded operation, and demand response.